Effects of Retinoic Acid and Insulin on Glycogen Content and Expression Levels of Glycogenic Proteins in Differentiating L6 Myocytes. (29th May 2020) - Armstrong, Aaron
Abstract: Objectives: The skeletal muscle is critical for the control of glucose homeostasis partially through glycogenesis. The effects of retinoic acid (RA) on glycogen content and expressions of key glycogenic proteins without or with insulin in L6 rat myocytes deserve to be studied. Methods: L6 myocytes at confluence were induced to differentiation using DMEM with 2% horse serum. Cells were incubated in medium with vehicle control or 1 μM RA without or with 10 nM insulin for 2, 4, and 6 days. Glycogen was extracted and analyzed using α-amyloglucosidase and released glucose assay. Proteins in cell lysates from parallel groups were extracted and subjected to analysis using western blotting. The expression levels of glycogen synthase (GS), phospho-glycogen synthase (Ser 641) (p-GS), glycogen synthase kinase 3-β(GSK3β), and phospho-glycogen synthase kinase 3-β (p-GSK3β) were determined using their specific antibodies, and then quantified with ImageJ software. Results: The RA + insulin group had higher glycogen content than the control group on days 2 to 6. A synergistic effect of RA and insulin were observed on day 2. GS expression was synergistically induced in the RA + insulin group on each day. The total p-GS normalized to β-actin in the RA + insulin group was higher than that in the control on day 2. However, the ratio of p-GS/GS in the RA + insulin group was lower than that in the control on day 2 and in RA group on day 6, respectively. GSK3β expression levels in insulin and RA + insulin groups were higher than that in the control on day two. The total p-GSK3β normalized to β-actin showed an increase in the insulin group compared to the RA group on day 6. The p-GSK3β/GSK3β ratio in the insulin group was higher than that in RA and RA + insulin groups on day 6. Conclusions: Treatments with RA and insulin increase the glycogen content in L6 cells via upregulation of glycogenesis. A synergy of RA and insulin can be seen. The increases of total GS and decreases of p-GS/GS ratio contribute to the elevation of GS activity. RA likely exerts its glycogenic effects through changes of the total GS level and phosphorylation by GSK3β. Funding Sources: Internal fund at the Univenrsity of Tennessee.